PERGESERAN MAKNA DALAM BUDAYA MBECEK DI DESA BANDUNG NGANJUK PRESPEKTIF TEORI SOLIDARITAS EMILE DURKHEIM - Thoriq, M Thoriqul Huda; Ita, Ita Purnama Sari; Zusril, Mokhamad Zusril (JURNAL ILMU BUDAYA, 2023)
Mbecek is a culture that has been integrated with society. Mbecek is a culture that has developed and continues to be preserved by the people of Bandung Village to this day. This tradition is routinely carried out by the people of Bandung when they hold a big event involving the local community as a sign that they have a big intention. The results of the study explain that the Mbecek Tradition carried out by the people of Bandung Village has several benefits including the Value of Solidarity, namely by carrying out this tradition the social ties of the community unite from various groups. The theological value is that they are grateful by carrying out the Mbecek Tradition as a form of expression of gratitude by maintaining good relations with God. T